The correlation between mother behavior and knowledge on the use of antibiotics in diarrheal children at Kedungreja, Cilacap - Fatimah, Vita; Kurniawati, Hidayatul (Science Midwifery, 2024)
In Southeast Asia, including Indonesia, antibiotic use is very high, reaching more than 80% in several provinces in Indonesia. This will lead to antibiotic resistance, one of the top three public health threats of the 21st century. Research needs to be carried out regarding the level of knowledge and behavior of mothers in using antibiotics for children's diarrhea. This was quantitative research with an analytical observational method with a cross sectional approach. Respondents filled out a questionnaire regarding their knowledge and behavior of using antibiotics which has been tested for validity and reliability. The data were analyzed using univariate and bivariate analysis using chi square. There were 100 people. The research results showed that most research subjects were mothers aged 26-30 years (29%). Based on the level of knowledge, most subjects were in the sufficient category (56%), and based on maternal behavior the majority were in the poor category (69%). There is no relationship between mother's knowledge and behavior in using antibiotics in children with diarrhea with a p value of 0.831. It can be concluded that here is no relationship between mother's knowledge and behavior in using antibiotics in children with diarrhea with a p value of 0.831.